REFORMASI HUKUM ISLAM DAN HAK ASASI MANUSIA PERSPEKTIF ABDULLAH AHMAD AN- NA’IM - Anis Hidayatul Imtihanah (IJoIS: Indonesian Journal of Islamic Studies, 2020)
This article explores the thoughts of Abdullah Ahmad An-Na'im regarding Islamic law and human rights enforcement. How does Islam answer contemporary problems, especially in the field of human rights. The main topic in the study conducted by Abdullah Ahmad An-Na'im was more based on the need to balance rights the rights of Muslims and non-Muslims as well as upholding the principle of equality, without gender discrimination, and in accordance with the concept of universalism contained in Islamic teachings which basically shows great concern for the main elements of humanity (al-insaniyyah). This research uses the library research method by examining various reference sources related to the human rights research model. Based on the results of research from various kinds of literature, it is explained that Abdullah Ahmad An-Na'im is one of the many Islamic figures and intellectuals who have sprung up bringing various new ideas and thoughts related to the re-actualization of Islamic law in the packaging of the modern syari'ah concept. This modern syari'ah concept says that when the historical shari'ah is confronted with modern public law, it will be found that in fact modern public law is more humanist and universal and is closely related to efforts to uphold human rights (human rights).